Research activities related to rational use of drugs by integral general physicians of Santiago de Cuba municipality - Leonardo Ramos Hernández; Frey Vega Veranes; Osmany Alonso Ayala; Armando Quintana Polanco; Iliana de la Caridad García Carrion (Revista Habanera de Ciencias Médicas)
Introduction: In the current context of the knowledge society, research occupies a primordial place as a fundamental way to inquiry and search for new knowledge.